Produção de monoacilgliceróis e diacilgliceróis via glicerólise enzimática e destilação molecular - Fregolente,Patricia Bogalhos Lucente; Pinto,Gláucia Maria F.; Wolf-Maciel,Maria Regina; Maciel Filho,Rubens; Batistella,César Benedito (Sociedade Brasileira de Química, 2009)
Monoacilglycerides and diacilglycerides are produced through lipase-catalyzed glycerolysis of soybean oil using Candida antarctica B in a solvent-free system. The reaction was carried out at a glycerol to triacylglycerol molar ratio of 8:1 with 2% of lipase. Acylglycerides, free fatty acids (FFA) and glycerol produced were separated employing the molecular distillation process. Starting from a product of enzymatic reaction 25.06% of triacylglycerols, 46.63% of diacylglycerides, 21.72% of monoacylglycerides, 5.38% of FFA and 1.21% of glycerol and after consecutively distillations, monoacylglycerides with 80% of purity was obtained and also oil with 54% of diacylglycerides to be used in human dietary.